Modelling methodologies for analysing critical infrastructures. Issue 2 (3rd April 2018) - Iturriza, Marta; Labaka, Leire; Sarriegi, Jose M.; Hernantes, Josune
Abstract: Critical Infrastructures (CIs) play a relevant role in both society and industry since they provide basic goods and services. CIs are interdependent on each other and a failure in one CI may spread rapidly to other dependent CIs. The resulting cascading effect leads to the amplification of the perturbation, giving rise to high-impact crises. Modelling and simulation methodologies have been suggested as suitable tools to properly analyse and assess the effect and consequences of crisis in CIs. This paper undertakes a systematic literature review to study which modelling methodologies are the most appropriate for analysing CIs, depending both on the CI sector and the scope of the modelling.